Translation and Adaptation of Cyberbullying Victimization and Perpetration Scales for Indonesian Contexts - Sabriani Borualogo, Ihsana; Kusdiyati, Sulisworo; Wahyudi, Hedi (KnE Social Sciences, 2023)
Cyberbullying incidents have increased intensively in Indonesia, affecting children’s mental health. However, no adapted and validated cyberbullying scales in Indonesian contexts were found. A systematic literature review presented several cyberbullying scales; one of them is cyberbullying victimization and cyberbullying perpetration scales that Patchin and Hinduja developed. Therefore, this study’s aims are twofold. First, to translate the two stated cyberbullying scales and adapt them for use in Indonesian contexts. Second, to test the validity and reliability of these two scales. This study’s methods include testing the translated scale for legibility and children’s understanding of the wording, conducting focus group discussions (FGDs) with three groups of children (N = 14), working on the back translation, and reviewing the back-translated version. This process also included pilot testing of the cyberbullying scales in children and adolescents aged 10-18 (N = 3,752; 52.4% girls; 47,6% boys; 81.6% middle school students; 18.4% high school students). Results showed that the Indonesian version of cyberbullying victimization and perpetration scales have been translated and adapted excellently and can be used for children aged 10 years and above. Keywords: adolescents, children, cyberbullying victimization scale, cyberbullying perpetration scale, Indonesia